2019
DOI: 10.4149/neo_2018_170929n619
|View full text |Cite
|
Sign up to set email alerts
|

The aberrant activation of the Wnt pathway caused by β-catenin mutation and its prognostic significance in NK/T-cell lymphoma

Abstract: The aberrant activation of the Wnt/β-catenin signal has an important role in the progression of cancers. Herein, we investigated β-catenin mutation and the activation of the Wnt pathway in association with the clinical-pathological characteristics, chemo-resistance and prognosis of NK/T-cell lymphoma (NKTCL). Real-time quantitative PCR, immunocytochemistry and immunohistochemistry SP methods detected the levels of β-catenin, c-myc and cyclin D1 in human NKTCL cell lines (SNK-6 and YTS) and NKTCL tissues. Mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[138]. It was reported that mutations in β-catenin exon 3 and the subsequent activation of Wnt pathway is associated with lower survival rate and poor prognosis of NK/T-cell lymphoma patients [139]. Use of genetically engineered NK cells as an effective antitumor treatment option for treating Renal Cell Carcinoma has attracted many scientists` attention.…”
Section: Nk Cells In Other Tumorsmentioning
confidence: 99%
“…[138]. It was reported that mutations in β-catenin exon 3 and the subsequent activation of Wnt pathway is associated with lower survival rate and poor prognosis of NK/T-cell lymphoma patients [139]. Use of genetically engineered NK cells as an effective antitumor treatment option for treating Renal Cell Carcinoma has attracted many scientists` attention.…”
Section: Nk Cells In Other Tumorsmentioning
confidence: 99%
“…MAPK/NF-κB pathway mediates high expression of the cytokine IL-2 and an inhibitory protein Programmed Death Ligand 1 (PD-L1), which positively correlates with chemoresistance (Bi et al, 2016;Wang et al, 2018). The oncogenic activation of the Wnt pathway often leads to poor response to chemotherapy in NKTCL patients (Qin et al, 2019a).…”
Section: Pro-tumorigenic Pathways Associated With Drug Resistance In Hematolymphoid Malignanciesmentioning
confidence: 99%